The impact of AI tools on the work and labour market prospects of programmers - Szabados, Levente (Vezetéstudomány / Budapest Management Review, 2025)
The significant advances in artificial intelligence (AI) solutions in the software industry are bringing profound changes that are not only reshaping the structure of the labour market but also significantly affecting the way programmers work and their job prospects. This paper examines the implications of the adoption of AI solutions in the software industry, with a particular focus on the work of programmers, from the perspective of economic sciences. The research applies questions developed from quantitative data to conduct a qualitative analysis (via in-depth interviews), focusing specifically on the experiences and perspectives of senior programmers but with an explicit emphasis on the ’generational’ problems between junior and senior professionals as well. The article aims to provide a comprehensive picture of how AI is affecting the roles, work practices and career prospects of professionals and analyse its wider impact on specific segments of programmers in the labour market.